2008
DOI: 10.1111/j.1574-6968.2007.00995.x
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR microspectroscopy: a promising method for the rapid identification ofListeriaspecies

Abstract: This work presents a pilot study to investigate the potential of fourier transform infrared (FT-IR) microspectroscopy for rapid identification of Listeria at the species level. Using this technique, FT-IR spectra were acquired from 30 strains from five Listeria species. The FT-IR spectra were analysed using stepwise canonical discriminant analysis and partial least-squares regression in a stepwise identification scheme. The results showed that 93% of all the samples were assigned to the correct species, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…In a proposed translational application we hope to identify not only the presence or absence of bacteria but also to identify a particular strain thus increasing the importance of improving Type II error. Previous studies have used spectroscopy to analyze biologic specimens [2,10,12,18,21]. Ngo-Thi et al [18] reported the ability of conventional FT-NIR spectroscopy in the MIR region and multivariate data analysis to correctly classify different nonbiofilm-associated bacteria in groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a proposed translational application we hope to identify not only the presence or absence of bacteria but also to identify a particular strain thus increasing the importance of improving Type II error. Previous studies have used spectroscopy to analyze biologic specimens [2,10,12,18,21]. Ngo-Thi et al [18] reported the ability of conventional FT-NIR spectroscopy in the MIR region and multivariate data analysis to correctly classify different nonbiofilm-associated bacteria in groups.…”
Section: Discussionmentioning
confidence: 99%
“…Reflectance spectroscopy provided a similar spectrum compared with conventional techniques in a nondestructive manner [21]. Janbu et al [10] showed that micro-FT-IR spectroscopy using stepwise canonical discriminant analysis could correctly identify strains of Listeria 93% of the time. Bosch et al [2] characterized Bordetella pertussis using spectroscopy and showed that planktonic bacteria have different spectra from its biofilm formation secondary to the spectroscopic absorbance of the glycocalyx or extracellular polymeric substances.…”
Section: Discussionmentioning
confidence: 99%
“…Species FTIRS, FTIRS-ATR, FTIR microspectroscopy CVA, ANN, SCDA, PLSRDA, PCA [5,[21][22][23][24][25]27,49,50] Lactobacillus spp. Species FTIRS HCA, ANN [31,32,39,40,53] Enterococcus spp.…”
Section: Bacteria Discrimination Level Infrared Technique Chemometricmentioning
confidence: 99%
“…It was demonstrated the advantage of using macrosamples instead of a microsample approach. [23] Janbu et al [24] also discriminated five Listeria species with FTIRS and FTIR micro-spectroscopy. Obtained discrimination success rates were approximately 93 and 100%, respectively.…”
Section: Bacteria Discrimination Level Infrared Technique Chemometricmentioning
confidence: 99%
“…During the last several decades, Fourier transform infrared (FTIR) spectroscopy has been extensively used as an effective tool to identify the chemical and molecular structure of different materials without the use of reagents [5][6][7][8][9][10][11][12][13]. Recently, advanced FTIR such as mid infrared (mid-IR) mercury cadmium telluride (MCT) detectors that provide high sensitivity and fast response time in a broad IR spectral range, have made it possible for the FTIR technique to detect and classify microorganisms in a rapid, reliable, and sensitive manner [5,6,8,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%